Inclusión y discapacidad visual. Aristas para el abordaje en educación superior - Ambrozio, Alan César (Editorial Bonaventuriana, Universidad de San Buenaventura Cali., 2022)
The raison d'être of this specialized work focuses on two areas: on the one hand, total visual impairment and visual weakness; and on the other hand, students with this differentiated ability at the higher education level. The literature in book format on educational inclusion has grown in recent years. In these works we can find topics on the explanation of educational inclusion, universal design, specific disabilities, classroom experiences at basic levels, among others. On visual impairment we find those related to socioemotional aspects, visual rehabilitation, orientation for parents, among others.